Morphological and molecular characterization of Ameloblastella pirarara sp. n. (Monogenoidea: Dactylogyridae) parasitizing the large Amazonian catfish Phractocephalus hemioliopterus. (September 2021) - Mathews, Patrick D.; Domingues, Marcus V.; Maia, Antônio A.M.; Silva, Marcia R.M.; Adriano, Edson A.; Aguiar, Julio C.
Abstract: In this study, integrative taxonomy is applied to describe a new dactylogyrid species, Ameloblastella pirarara sp. n. from the gills of Phractocephalus hemioliopterus, a commercially and ecologically important Amazonian catfish. Ameloblastella pirarara sp. n. can be distinguished from its congeners mainly by the morphology of the male copulatory organ (MCO), accessory piece, and anchors. The new species most resembles Ameloblastella unapi, from the Peruvian Amazon, but differs from it by the number of MCO rings, morphology of the vaginal canal and sclerotized structures of the haptor. Phylogenetic analyses based on sequences of the partial 28S rDNA (D1-D2 domains) gene placed the new species in a well-supported subclade of Ameloblastella spp. parasites of Neotropical siluriform fish, as a sister taxon to Ameloblastella unapioides . Thus, the new species described herein expands our knowledge of the diversity of monogenoid parasites from Amazonian freshwater fish. Graphical abstract: Image 1 Highlights: A new monogenean is described infesting a commercial and ecological important fish, Phractocephalus hemioliopterus. Ameloblastella pirarara sp. n. is described based on morphological and molecular data. Phylogenetic analysis placed the newly monogenean species in a well-supported subclade of Ameloblastella parasites of siluriform fish.